BEHAVIOR AND ATTITUDES OF FEMALE MEDICAL STUDENTS REGARDING MENSTRUAL PRODUCTS - Marković, Teodora; Marušić, Vuk; Nikolić, Aleksandra; Vujčić, Isidora; Bjekić, Milan; Šipetić Grujičić, Sandra (HEALTH CARE, 2024)
Introduction/Aim: According to the data of the World Bank, period poverty affects about 500 million women worldwide. Inadequate sanitary conditions and the unavailability of menstrual products, as well as their inadequate use, can lead to serious disorders of women's health. The aim of this study was to analyze the behavior and attitudes of female medical students regarding menstrual products.Methods: The cross-sectional study was conducted at the Faculty of Medicine of the University of Belgrade, in the period 16-29 May 2024. year. The sample consisted of 277 medical students. Data were collected using a questionnaire. The χ2 test was used for the statistical analysis of data.Results: 5.1% of female students had problems with obtaining menstrual products during the last 12 months. Statistically significantly more often this problem was experienced by older than younger female students, while a statistically significant difference was not observed between female students with a permanent place of residence in the city and female students with a permanent place of residence in the countryside, as well as between female students of I-III and IV-V years of study. In such situations, 1.4% of female students used a substitute for a given menstrual product (eg cloth, toilet paper, etc.), 1.8% borrowed menstrual products from friends, relatives, etc., 1.1% used menstrual products for longer than they usually do and 4.7% bought cheaper menstrual products. The majority of female students (97.8%) expressed their wish for all school girls and female students in Serbia to have free products necessary for maintaining hygiene during menstruation. Conclusion: It is necessary to continuously examine the behavior and attitudes of female students regarding menstrual products and the factors associated with them, both at the Faculty of Medicine of the University of Belgrade and at all other faculties, and use the results obtained as a basis for the creation and implementation of activities aimed at preserving and improving the health and quality of life of female students.
Keywords: Period, Menstruation, Menstrual health, Menstrual Health Management, Period poverty